A theoretical perspective of reading in English second language classrooms (Namibian Journal of Linguistics, Literature and Communication Studies, 2023)
Several language experts have proposed language models that provide a solid foundation for effective second language acquisition. This paper aims to review language theories and explain their relevance to English Second Language (ESL) learning through reading. The ultimate goal is to develop theoretical measures whose considerations and implementations could motivate learners to read more in order to effectively learn ESL, thereby improving academic performance. This paper highlights three theoretical lenses that contribute to the understanding of second language acquisition through reading, namely social constructivism, the input hypothesis, BICS and CALP theory. The study discovered that reading instruction in ESL should be practiced through a combination of multimodality, social interaction, and comprehensive input. The integration and use of appropriate technologies in ESL classrooms, teachers' awareness of their learners' developmental level, exposure to challenging reading materials, and the development of learners' critical thinking skills are all necessary components of second language acquisition. These components should be executed properly in the reading lessons for the learners to acquire ESL to the degree of proficiency.
Keywords: Acquisition, BICS and CALP theory; input hypothesis; language theories, language learning; second language; social constructivism